Synthesis of Thiadiazoles and 1,2,4-Triazoles Derived from Cyclopropane Dicarboxylic Acid . - Sharba, A. Hussain K. (Molecules, 2005)
New heterocyclic derivatives of cyclopropane dicarboxylic acid comprising thiadiazole and 1,2,4-triazole moieties are reported. Reaction of 1,1-cyclopropane dicarboxylic acid (1) with thiosemicarbazide and phosphorous oxychloride resulted in 1,1-bis (2-amino-1,3,4-thiadiazol-5- yl)cyclopropane (2). Cyclopropane dicarboxylic acid thiosemicarbazide (6) was converted into 1,1-bis(3-thio-4H-1,2,4-triazol-5-yl) cyclo- propane (7) by ring closure in an alkaline medium. The thiadiazole 2 and the triazole 7 were converted into a variety of derivatives.